Temporal and spatial distributions of cold-water corals in the Drake Passage: Insights from the last 35,000 years - Margolin, Andrew R.; Robinson, Laura F.; Burke, Andrea; Waller, Rhian G.; Scanlon, Kathryn M.; Roberts, Mark L.; Auro, Maureen E.; van de Flierdt, Tina (Deep Sea Research Part II: Topical Studies in Oceanography, 2014)
Scleractinian corals have a global distribution ranging from shallow tropical seas to the depths of the Southern Ocean. Although this distribution is indicative of the corals having a tolerance to a wide spectrum of environmental conditions, individual species seem to be restricted to a much narrower range of ecosystem variables. One way to ascertain the tolerances of corals, with particular focus on the potential impacts of changing climate, is to reconstruct their growth history across a range of environmental regimes. This study examines the spatial and temporal distribution of the solitary scleractinian corals Desmophyllum dianthus, Gardineria antarctica, Balanophyllia malouinensis, Caryophyllia spp. and Flabellum spp. from five sites in the Drake Passage which cross the major frontal zones. A rapid reconnaissance radiocarbon method, cooupled with U-Th dating, extends the age range back more than 100 thousand. Within this age range there are distinct changes in the temporal and spatial distributions of these corals, both with depth and latitude, and on millennial timescales. Two major patterns that emerge are: 1) D. dianthus populations show clear variability in their occurrence through time depending on the latitudinal position within the Drake Passage. North of the Subantarctic Front, D. dianthus first appears in the late deglaciation (~17,000 years ago) and persists to today. South of the Polar Front, in contrast, populations existed during the glacial and early deglacial periods, with only few modern occurrences. A seamount site between the two fronts exhibits characteristics similar to both the north and south sites. This shift across the frontal zones within one species cannot yet be fully explained, but it is likely to be linked to changes in surface productivity, subsurface oxygen concentrations, and carbonate saturation state. 2) at locations where multiple genera were dated, clear differences in age and depth distribution of the populations provide clear evidence that each genus has unique environmental requirements to sustain its population.
id: 2278

Reconnaissance dating A new radiocarbon method applied to assessing the temporal distribution of Southern Ocean deep-sea corals - Burke, Andrea; Robinson, Laura F.; McNichol, Ann P.; W. J. Jenkins; Scanlon, Kathryn M.; Gerlach, Dana S. (Deep-Sea Research Part I-Oceanographic Research Papers, 2010)
We have developed a rapid reconnaissance method of preparing graphite for (14)C/(12)C analysis Carbonate (similar to 15 mg) is combusted using an elemental analyzer and the resulting CO(2) is converted to graphite using a sealed tube zinc reduction method Over 85% (n=45 replicates on twenty-one individual corals) of reconnaissance ages measured on corals ranging in age from 500 to 33 000 radiocarbon years (Ryr) are within two standard deviations of ages generated using standard hydrolysis methods on the same corals and all reconnaissance ages are within 300 Ryr of the standard hydrolysis ages Replicate measurements on three individual aragonitic corals yielded ages of 1076 +/- 35 Ryr (standard deviation n=5) 10 739 +/- 47 Ryr (n=8) and 40 146 +/- 3500 Ryr (n=9) No systematic biases were found using different cleaning methods or variable sample sizes Analysis of (13)C/(12)C was made concurrently with the (14)C/(12)C measurement to correct for natural fractionation and for fractionation during sample processing and analysis This technique provides a new rapid method for making accurate percent-level (14)C/(12)C analyses that may be used to establish the rates and chronology of earth system processes where survey-type modes of age estimation are desirable For example applications may include creation of sediment core-top maps preliminary age models for sediment cores and growth rate studies of marine organisms such as corals or mollusks We applied the reconnaissance method to more than 100 solitary deep-sea corals collected in the Drake Passage in the Southern Ocean to investigate their temporal and spatial distribution The corals used in this study are part of a larger sample set and the subset that was dated was chosen based on species as opposed to preservation state so as to exclude obvious temporal biases Similar to studies in other regions the distribution of deep-sea corals is not constant through time across the Drake Passage Most of the corals from the Burdwood Bank (continental shelf of Argentina) have ages ranging between 0 and 2500 calendar years whereas most of the corals from the Sars Seamount in the Drake Passage have ages between 10 000 and 12 500 calendar years Such differences may be caused in part by sampling biases but may also be caused by changes in larval transport nutrient supply or other environmental pressures (C) 2010 Elsevier Ltd All rights reserved
id: 1924; PT: J; UT: WOS:000284750700012